1987
DOI: 10.1111/j.1365-246x.1987.tb05243.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of shear-waves from shots in anisotropic media

Abstract: A complex array of vertical-seismic-profiles and reflection surveys in the Taman Peninsula, Krasnodar, using geophones with inclined axes, is used to investigate shear-wave splitting in thick Maikopian clays characterised by pronounced diapirism. The shear waves split into SH (faster) and SV (slower) components and display transverse isotropy with a vertical axis of symmetry with a maximum shear-wave delay of up to 0.5 s. Within the accuracy of the observations there is no azimuthal anisotropy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…This had been suspected in the past (Turcotte 1992), but this is now a direct correlation with other phenomena. (Hess 1964) and continents (Bamford 1977) Anisotropy observed (Crampin 1966) and calculated in higher-mode surface-wave dispersion (Crampin and King 1977) Shear-wave splitting first named (as S-wave splitting) and displayed in synthetic seismograms (Keith and Crampin 1977c) 1IWSA 1982 Observations of P-wave velocity anisotropy in field and laboratory (Artemieva and Chesnokov 1991;Brodov et al 1991;Brown et al 1991;de Parscau 1991;MacBeth 1991a, b) Elastic moduli calculated for aligned cracks (Crampin 1978(Crampin , 1984b Importance of shear-wave window above small earthquakes recognised (Evans 1984) Aligned microcracks (EDA cracks) suggested in most crustal rocks ) General behaviour of wave propagation in cracked media reviewed (Crampin 1981) Shear-wave splitting displayed in synthetic seismograms through cracked media (Crampin 1978) Shear-wave splitting observed above earthquakes in both crust (Crampin et al 1980) and upper mantle (Ando et al 1980) 2IWSA 1986 1987 Observations of P-wave anisotropy in crust Galperina and Galperin 1987) Speculation on how monitoring shear-wave splitting could predict earthquakes (Chen et al 1987) Determination of the Thomsen parameters for seismic exploration (Thomsen 1986) Double-contour integration for 3D full-wave propagation in anisotropic substrates (Taylor 1987) 3IWSA 1988 Observations of anisotropy in laboratory studies in both field and laboratory (Kaneshima 1990;Savage et al 1990;Shih and Meyer 1990) First attempts at automatic measurement of shear-wave splitting (Shih and Meyer 1990) First correlation of microcracks with fractures and directions of preferred fluid flow (Queen and Rizer 1990) Shear-wave splitting time delays seen to increase before two earthquakes ) ANISEIS programme developed for applying double-contour integration for full-wave synthetic seism...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This had been suspected in the past (Turcotte 1992), but this is now a direct correlation with other phenomena. (Hess 1964) and continents (Bamford 1977) Anisotropy observed (Crampin 1966) and calculated in higher-mode surface-wave dispersion (Crampin and King 1977) Shear-wave splitting first named (as S-wave splitting) and displayed in synthetic seismograms (Keith and Crampin 1977c) 1IWSA 1982 Observations of P-wave velocity anisotropy in field and laboratory (Artemieva and Chesnokov 1991;Brodov et al 1991;Brown et al 1991;de Parscau 1991;MacBeth 1991a, b) Elastic moduli calculated for aligned cracks (Crampin 1978(Crampin , 1984b Importance of shear-wave window above small earthquakes recognised (Evans 1984) Aligned microcracks (EDA cracks) suggested in most crustal rocks ) General behaviour of wave propagation in cracked media reviewed (Crampin 1981) Shear-wave splitting displayed in synthetic seismograms through cracked media (Crampin 1978) Shear-wave splitting observed above earthquakes in both crust (Crampin et al 1980) and upper mantle (Ando et al 1980) 2IWSA 1986 1987 Observations of P-wave anisotropy in crust Galperina and Galperin 1987) Speculation on how monitoring shear-wave splitting could predict earthquakes (Chen et al 1987) Determination of the Thomsen parameters for seismic exploration (Thomsen 1986) Double-contour integration for 3D full-wave propagation in anisotropic substrates (Taylor 1987) 3IWSA 1988 Observations of anisotropy in laboratory studies in both field and laboratory (Kaneshima 1990;Savage et al 1990;Shih and Meyer 1990) First attempts at automatic measurement of shear-wave splitting (Shih and Meyer 1990) First correlation of microcracks with fractures and directions of preferred fluid flow (Queen and Rizer 1990) Shear-wave splitting time delays seen to increase before two earthquakes ) ANISEIS programme developed for applying double-contour integration for full-wave synthetic seism...…”
Section: Discussionmentioning
confidence: 99%
“…Three papers reported various observations of anisotropic effects in USSR, including the very detailed multi-azimuth reflection surveys and vertical seismic profiles (VSPs) in transverse isotropy by Galperina and Galperin (1987).…”
Section: Interpretation-aligned Cracksmentioning
confidence: 99%
“…It can be caused by layering as well as by intrinsic, microscopic properties of the rocks. Investigation on sediments have shown that large anisotropy effects are caused by clay (Brodov et al 1984;Galperina & Galperin 1987). The percentage of clay in a sediment is correlated with the anisotropic property of the sediment, which can hence serve as a lithology indicator (Winterstein 1986).…”
Section: Introductionmentioning
confidence: 99%